2017
DOI: 10.3389/fnsys.2017.00075
|View full text |Cite
|
Sign up to set email alerts
|

Gene Network Construction from Microarray Data Identifies a Key Network Module and Several Candidate Hub Genes in Age-Associated Spatial Learning Impairment

Abstract: As humans age many suffer from a decrease in normal brain functions including spatial learning impairments. This study aimed to better understand the molecular mechanisms in age-associated spatial learning impairment (ASLI). We used a mathematical modeling approach implemented in Weighted Gene Co-expression Network Analysis (WGCNA) to create and compare gene network models of young (learning unimpaired) and aged (predominantly learning impaired) brains from a set of exploratory datasets in rats in the context … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 135 publications
0
6
0
Order By: Relevance
“…Previous results suggest a potential effect of DPP6 on intellectual function and memory formation (Lin et al, 2013 ; Uddin and Singh, 2017 ). Accordingly, in the present study, we found that DPP6-KO mice show clear deficits in spatial learning/memory phase of the Morris water maze, T-maze, and object recognition memory (Figures 1 – 3 ).…”
Section: Discussionmentioning
confidence: 89%
“…Previous results suggest a potential effect of DPP6 on intellectual function and memory formation (Lin et al, 2013 ; Uddin and Singh, 2017 ). Accordingly, in the present study, we found that DPP6-KO mice show clear deficits in spatial learning/memory phase of the Morris water maze, T-maze, and object recognition memory (Figures 1 – 3 ).…”
Section: Discussionmentioning
confidence: 89%
“…In a co-expression network, hub genes are defined as genes inside co-expression modules that have high connectivity (Langfelder and Horvath, 2008). Hub genes are highly co-expressed with other genes and play key roles in critical pathways (Uddin and Singh, 2017). To identify the hub genes of the three target modules, intramodular connectivity and module membership for all genes in each module were calculated using the WGCNA package.…”
Section: Resultsmentioning
confidence: 99%
“…Rice is an ideal model to study the regulation of gene expression in response to different stresses (Rabbani et al, 2003;Yazaki et al, 2003). Based on previous research performed, auxin and abscisic acid are the most important phytohormones in response to different hormonal stresses (Uddin and Singh, 2017). ABA has an important factor in the response of plants to abiotic stresses.…”
Section: Introductionmentioning
confidence: 99%